Penanaman Nilai Nilai Pendidikan Islam Multikultural Melalui Kajian Kitab Kuning dalam Membangun Keharmonisan Sosial Santri - Halimah, Siti Nur; Shalahuddin, Shalahuddin (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article aims to find out how to instill multicultural values through the study of the yellow book at the al-Inayah Tebo Islamic Boarding School. The important question to be answered is why can the study of the yellow book be used as an alternative to instilling multicultural values in students? This article comes from qualitative research using data collection through observation, interviews and documentation. The research results show that the yellow book material taught sorogan and bandongan can build multicultural values such as tolerance, democratic values, equality values, and justice values in the daily lives of students. These values in turn can increase the harmonious life of the students at the Al Inayah Tebo Islamic boarding school. Artikel ini bertujuan mengetahui bagaimana penanaman nilai-nilai multikultural melalui kajian kitab kuning di Pesantren al-Inayah Tebo. Pertanyaan penting yang hendak dijawab adalah mengapa kajian kitab kuning dapat dijadikan alternatif penanaman nilai-nilai multikultural para santri? Artikel ini berasal dari penelitian kualitatif dengan pengumpulan data secara observasi, wawancara, dan dokumentasi. Hasl penelitian menunjukkan bahwa materi kitab kuning yang diajarkan yang secara sorogan dan bandongan dapat membangun nilai-nilai multikultural seperti teloransi, nilai demokrasi, nilai kesetaraan, serta nilai keadilan dalam kehidupan sehari-hari santri. Nilai-nilai ini pada gilirannya dapat meningkatkan keharmonisan hidup para santri di pesantren Al Inayah Tebo.